OVERCOMING GRAMMAR DIFFICULTIES IN TEACHING ENGLISH TO YOUNG LEARNERS - Mardonova Ra’no; Abdinavidov Shopo’lat (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Teaching English grammar to young learners presents educators with multifaceted challenges that require nuanced and comprehensive approaches to ensure effective language acquisition and proficiency. This expansive study explores in-depth the various obstacles and hurdles faced by teachers when imparting grammar concepts to children within the English language learning context. Drawing from a rich tapestry of pedagogical tools and methodologies, including but not limited to engaging activities, innovative visual aids, immersive contextual learning experiences, strategically designed scaffolding techniques, nuanced feedback mechanisms, and reinforcement strategies, this research endeavors to provide an exhaustive and thorough analysis of the most effective practices in the domain.